2000
DOI: 10.1007/pl00011313
|View full text |Cite
|
Sign up to set email alerts
|

Helium–Neon Laser Irradiation: Effect on the Experimental Pain Threshold

Abstract: The aim of this double-blind study was to examine the e#ects of helium-neon laser irradiation on the mechanical (pressure algometry) and electrical (1 ms monophasic square-wave pulses, 50 Hz) pain threshold. 32 pain-free subjects were randomly assigned to either the experimental group (helium-neon laser stimulation: 5 mW, 10 min) or the placebo group (sham stimulation). Laser or sham stimulation and pain threshold ascertainment were carried out on the dorsal aspect of the forearm area. The contralateral arm se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Seven studies found none, or only minor, changes in neurophysiological processes or nerve conduction velocities in intact peripheral nerves after LLLT. 20,[25][26][27][28][29][30] One study in healthy subjects found LLLT reduced nerve conduction velocity and increased negative peak latency with energy dose of 1 Joule per stimulation point, but there were no effects from energy doses at 0.5 or 1.5 Joules when applied over the sural nerve. 31 There was no convincing evidence that LLLT could act by substantial rapid modulation of neurophysiological processes in intact peripheral nerves in the absence of inflammation.…”
Section: Laboratory Studiesmentioning
confidence: 96%
“…Seven studies found none, or only minor, changes in neurophysiological processes or nerve conduction velocities in intact peripheral nerves after LLLT. 20,[25][26][27][28][29][30] One study in healthy subjects found LLLT reduced nerve conduction velocity and increased negative peak latency with energy dose of 1 Joule per stimulation point, but there were no effects from energy doses at 0.5 or 1.5 Joules when applied over the sural nerve. 31 There was no convincing evidence that LLLT could act by substantial rapid modulation of neurophysiological processes in intact peripheral nerves in the absence of inflammation.…”
Section: Laboratory Studiesmentioning
confidence: 96%
“…Mester 11 showed in his pioneering work in 1966 that LLLT presented beneficial effects on tissue; since then, other researchers have found that LLLT affects tissue healing, 12,13 anti-inflammatory action, and analgesic effects. [16][17][18][19] Although different studies have shown the efficacy of that treatment, particularly of inflammatory pain, the mechanism by which radiation produces analgesia and anti-inflammatory effects remains elusive. Previous studies in the 1980s suggested that laser radiation could promote release of neurotransmitters, such as serotonin 19 or ␤-endorphin.…”
Section: Introductionmentioning
confidence: 99%
“…Schuhfried et al 32 relataram que o PPT pode ser influenciado pela sensibilização dos nociceptores pelas medidas aferidas rapidamente, uma após a outra. Como todos os grupos estudados apresentaram-se negativos, pode ter havido uma sensibilização na região da perna.…”
Section: Discussionunclassified
“…Porém, há uma carência de estudos que utilizaram a mesma metodização deste estudo com sujeitos saudáveis e com a algometria por pressão. O único trabalho encontrado foi o de Schuhfried et al 32 , os quais não observaram diferença no PPT nos sujeitos saudáveis comparado com o Grupo Placebo, o que corrobora com este estudo quando comparado com as energias de 6 e 12 J por ponto. Também utilizou-se uma energia de 3 J por ponto, porém com um laser de hélio neônio (λ=632,8 nm, Pm=5 mW).…”
Section: Dados Do Limiar De Dor Por Pressãounclassified
See 1 more Smart Citation